IMPLEMENTASI KEBIJAKAN PENCEGAHAN DAN PENANGGULANGAN DEMAM BERDARAH DENGUE DI KECAMATAN BEKASI UTARA - Arta Nurulhuda, Arisa; Widowati, Nina; Maesaroh, Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
One measure of a country's success can be seen from the country's ability to create policies and then implement them to overcome the problems faced by society, especially in the health sector. This proves that the government needs to make innovative policies and implement these policies to reduce the number of dengue hemorrhagic fever (DHF) cases. In its implementation, there are still problems that show that the government is not yet optimal in implementing dengue fever prevention and control policies in North Bekasi District. The aim of this research is to analyze the implementation of dengue hemorrhagic fever prevention and control policies based on Bekasi Mayor's Instruction Number: 440/94/Dinkes 2019 in North Bekasi District and identify supporting and inhibiting factors for the implementation of dengue hemorrhagic fever prevention and control policies in Bekasi District North. This research uses descriptive research methods with a qualitative approach. The technique for determining informants in this research is purposive sampling with data collection methods through observation, interviews, documentation and triangulation. This research looks at the 5 accuracy of Riant Nugroho's policy implementation, namely policy accuracy, implementation accuracy, target accuracy, environmental accuracy, and process accuracy. The research results show that there is still an increase in the number of dengue fever cases, a lack of widespread socialization, a lack of public awareness regarding the importance of dengue fever, the involvement of political elites resulting in a lack of supervision in the implementation of fogging, and a lack of resources. It is recommended that the government be more consistent in implementing policies to prevent and control dengue hemorrhagic fever by optimizing the movement to eradicate mosquito nests in the community so that the policy can be implemented well.